2019
DOI: 10.2196/12130
|View full text |Cite
|
Sign up to set email alerts
|

Do-It-Yourself Gamified Cognitive Training: Viewpoint

Abstract: Cognitive decline is an important nonmotor symptom in Parkinson disease (PD). Unfortunately, very few treatment options are available. Recent research pointed to small positive effects of nonpharmacological cognitive training in PD. Most of these trainings are performed under supervision and solely computerized versions of (traditional) paper-pencil cognitive training programs, lacking rewarding gamification stimulants that could help to promote adherence. By describing 3 different self-invented ways of cognit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 41 publications
(54 reference statements)
0
10
0
Order By: Relevance
“…Intervention feasibility criteria are mostly met, but improvements are needed in order to increase usability. Even if online gamified CT may not be suitable for all patients, many PD patients are interested in such interventions [6], increasing the need to further investigate the efficacy of gamified CT in larger PD trials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intervention feasibility criteria are mostly met, but improvements are needed in order to increase usability. Even if online gamified CT may not be suitable for all patients, many PD patients are interested in such interventions [6], increasing the need to further investigate the efficacy of gamified CT in larger PD trials.…”
Section: Discussionmentioning
confidence: 99%
“…CT appears to be safe and cost-effective in PD, with modest positive effects on executive functions and working memory [5]. Gamification may further enhance traditional CT in terms of attractiveness and adherence [6], thereby making patients more inclined to continue playing, increasing possible treatment effectiveness, and maintaining benefits over time. So far, the merits of gamified CT have never been investigated in PD patients.…”
Section: Introductionmentioning
confidence: 99%
“…The review concluded that gamified training is highly engaging and motivational and found evidence that gamification may be effective at enhancing CT in the elderly and ADHD populations ( Lumsden et al, 2016 ). Similarly, recently, the Parkin’Play study showed enhanced global cognition scores after 24-weeks of individuals with PD participating in a home-based, gamified CT intervention ( Van De Weijer et al, 2019 ).…”
Section: Introductionmentioning
confidence: 90%
“…Given that individuals with PD experience decreased reward sensitivity in an off-dopaminergic medication state, as well as increased apathy ( Muhammed et al, 2016 ), this may be a particularly relevant concern for use of CT in this population. One strategy that may improve engagement is the addition of game-like features (gamification) into CT programs ( Lumsden et al, 2016 ; Van De Weijer et al, 2019 ). This can be attributed to the incorporation of features such as high-score and reward incentives, narrative, personalization, self-directed challenge, exploration, free-play, competition and graphics into the training platform ( Nagle et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…These are particularly important for the PD population, where patients have a decreased reward sensitivity in an off-dopaminergic medication state, as well as increased apathy ( Muhammed et al, 2016 ). Therefore, enhancement of the rewarding elements of game play may improve perceived self-efficacy, motivation and adherence, subsequently improving outcomes ( Van De Weijer et al, 2019 ). Whilst this area of CT adaptation is in its infancy, one recent 2020 study investigated the efficacy of a gamified CT program called “Parkin’Play” in a cohort of PD-MCI patients ( n = 21) against a no-intervention waitlist control ( n = 20).…”
Section: The Use Of Adaptive and Assistive Technology To Deliver Ct In Pdmentioning
confidence: 99%